Electron tomography of the contact between T cells and SIV/HIV-1: implications for viral entry. - Rachid Sougrat; Alberto Bartesaghi; Jeffrey D Lifson; Adam E Bennett; Julian W Bess; Daniel J Zabransky; Sriram Subramaniam (PLoS Pathogens)
The envelope glycoproteins of primate lentiviruses, including human and simian immunodeficiency viruses (HIV and SIV), are heterodimers of a transmembrane glycoprotein (usually gp41), and a surface glycoprotein (gp120), which binds CD4 on target cells to initiate viral entry. We have used electron tomography to determine the three-dimensional architectures of purified SIV virions in isolation and in contact with CD4+ target cells. The trimeric viral envelope glycoprotein surface spikes are heterogeneous in appearance and typically approximately 120 A long and approximately 120 A wide at the distal end. Docking of SIV or HIV-1 on the T cell surface occurs via a neck-shaped contact region that is approximately 400 A wide and consistently consists of a closely spaced cluster of five to seven rod-shaped features, each approximately 100 A long and approximately 100 A wide. This distinctive structure is not observed when viruses are incubated with T lymphocytes in the presence of anti-CD4 antibodies, the CCR5 antagonist TAK779, or the peptide entry inhibitor SIVmac251 C34. For virions bound to cells, few trimers were observed away from this cluster at the virion-cell interface, even in cases where virus preparations showing as many as 70 envelope glycoprotein trimers per virus particle were used. This contact zone, which we term the "entry claw", provides a spatial context to understand the molecular mechanisms of viral entry. Determination of the molecular composition and structure of the entry claw may facilitate the identification of improved drugs for the inhibition of HIV-1 entry.